BIOETHANOL AS AN ALTERNATIVE ENERGY RESOURCE - P.BANGARAIAH; P.ASHOK KUMAR (International Journal of Pharma and Bio Sciences, 2014)
Bioethanol is widely recognized these days as a very promising alternative source of energy Biomass is considered as an safe and clean material with unlimited availability and high potential to be used as a renewable source for the production of energy and alternative fuels. Biofuel derived from renewable feed stocks are environmentally friendly fuels. The process of turning coal into liquid produces more carbon dioxide emissions than conventional gasoline does. This work suggests that bioethanol produced from potato peel is the best alternative fuel and this also avoid the environmental pollution problem.